2006
DOI: 10.1542/peds.2005-1079
|View full text |Cite
|
Sign up to set email alerts
|

Influenza Vaccinations of Young Children Increased With Media Coverage in 2003

Abstract: OBJECTIVE. We sought to evaluate the impact of intense influenza media coverage during the 2003–2004 influenza season on the influenza vaccination status of children 6 to 59 months of age. METHODS. Children 6 to 59 months of age who presented to a large, academic pediatric continuity clinic or affiliated acute care clinic in the summer of 2004 were enrolled. A parental survey ascertained the influenza vaccination status of the child and family members during the 2003–2004 influenza season and fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
66
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 10 publications
(15 reference statements)
2
66
0
Order By: Relevance
“…Less research has assessed the effects of information about the course of an infectious disease outbreak on desire for vaccination, although at least one study has suggested that media reporting about the unexpected severity of a flu outbreak played a larger role in driving uptake of the vaccine than vaccine-specific reporting. 21 Several studies have suggested that media reporting about features of an outbreak, such as the number of cases or deaths, might influence key health behaviours. 9,19,60,67 However, we found no evidence to suggest that how much people had heard about swine flu in the past week affected likely vaccine uptake or that specific aspects of what they had heard had any substantial impact.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Less research has assessed the effects of information about the course of an infectious disease outbreak on desire for vaccination, although at least one study has suggested that media reporting about the unexpected severity of a flu outbreak played a larger role in driving uptake of the vaccine than vaccine-specific reporting. 21 Several studies have suggested that media reporting about features of an outbreak, such as the number of cases or deaths, might influence key health behaviours. 9,19,60,67 However, we found no evidence to suggest that how much people had heard about swine flu in the past week affected likely vaccine uptake or that specific aspects of what they had heard had any substantial impact.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 Reporting by these news sources has long been recognised as a key factor that can affect people's health-related behaviours and have both positive and negative consequences for the public's health. [16][17][18][19][20][21][22] One way in which the media exert these effects is by 'setting the agenda'. The theory of agenda setting suggests that the more coverage an issue receives, regardless of the nature of that coverage, the more important it becomes to members of the public.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[23][24][25] Confirmed by earlier publications, several factors were associated with increased influenza vaccinations, including any practice visit from October through January. 26 Also, children aged 6-11 months were more likely to be vaccinated than children aged 18-23 months. 27 Whether this difference was due to providers more frequently reviewing vaccination status in younger than older children or more frequent visits in younger children is unknown.…”
Section: Discussionmentioning
confidence: 97%
“…They concluded that there was a limited influence of mainstream media on MMR vaccinations in the U.S.A. Mason and Donnely [9] observed that in the period 1997-1998 the vaccination uptake in Wales was lower in areas where a series of anti-MMR vaccine articles had been published, than areas where they had not been published. Ma et al [11] concluded that media coverage together with recommendations from physicians were associated with increased influenza vaccination coverage in young children. Finally Kelly et al [7] looked at the relationship between media exposure and knowledge about the HPV vaccine.…”
Section: Related Workmentioning
confidence: 99%